Regietheater in Performance - Risi, Clemens (Wagner in Context, 2024)
Since the arrival of Regietheater in opera, beginning in the 1970s, the possibilities, limits, and demands of stage directing in opera have been a topic of debate. Regietheater both maintains opera’s musical dramaturgy and radically questions, re-examines, and recontextualises the transmitted and ascertainable strata of meaning in the available texts (libretto, score, discourse on the staging history). By discussing some exemplary moments and striking characteristics of Regietheater productions of the Wagnerian repertoire (e.g., by Harry Kupfer, Peter Konwitschny, Katharina Wagner), the chapter argues that such productions are necessary for keeping the well-known repertoire alive. The chapter is not meant as an overview of current staging practices of the Wagnerian repertoire, nor as a best-of list for Regietheater productions; it is rather an attempt to highlight some of the possible effects of those productions.
CRIS-Team Scopus Importer:2025-10-16
Keywords: Corporeality; Opera in performance; Regietheater; Stage and media technologies